Quality Control Analysis with Statistical Process Control (SPC) and Failure Mode Effect Analysis (FMEA) Methods on Battery Products at PT. Selatan Jadi Jaya - Putra, I Dewa Gede Rama; Sumiati, Sumiati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. Selatan Jadi Jaya is a company that produces lead acid batteries for Automotive Car Batteries. During production, problems often arise, namely the high level of product defects. These defects more often appear in the burning process, including Melted Tin defects, Burnt Connector defects, Bent Plate defects, and Torn Separator defects. The purpose of this study is to determine the percentage of defects that occur most often and the factors that cause defects and provide suggestions for improving the quality of battery batteries. Based on the above problems, quality control analysis can use methods, namely the Statistical Process Control (SPC) method and improvement efforts using Failure Mode and Effect Analysis (FMEA). Based on the results of research on Statistical Process Control that the dominant defect is Burnt Connector with a percentage of (33%), then followed by Plate Bent by (26%), then Melted Tin by (24%), and Torn Separator by (17%). Based on the results of the Failure Mode and Effect Analysis research, it is known that the highest RPN value is 200 on the tin melt defect with the cause of failure due to errors when workers set the fire too large. The recommendation for improvement for this problem is to adjust the size of the fire in accordance with the procedures set before welding.